Comparative Study of Contextual Islamic Education: Fazlur Rahman and Quraish Shihab - Wahyu Sihab; Muhammad Fahrur Rozi (Peradaban Journal of Religion and Society, 2025)
The purpose of this research is to compare and contrast the writings of Fazlur Rahman and Quraish Shihab to develop contextual Islamic education. They are known as contemporary Islamic figures who strive to make Islamic teachings relevant in the modern world. This research uses Qualitative-Descriptive method with Systematic Literature review. The results show that through historiography and the double movement method, Fazlur Rahman emphasizes the importance of ijtihad and rationalism in Islamic education, while Quraysh Shihab uses a thematic-humanistic approach to emphasize the value of inclusivity, diversity, and spiritual-social balance. This study shows that despite their differences, both share the same vision in viewing Islamic education as a means to foster human dignity, critical thinking and resilience. This makes a conceptual contribution to the development of a more flexible, humanist and transformative Islamic education paradigm and encourages the integration of Qur'anic teachings in a global context.